CAP: CAP - Jankovic, Jelena; Jandrić, Aleksandar; Jordanova, Elena (Halo 194 Scientific Journal of Emergency Medicine, 2023)
Pneumonia is one of the most common diseases of modern medicine. It represents the inflammation of the lung parenchyma, caused by various toxins or agents. It is present in both sexes equally, but occurs more often in elderly people, immunocompromised people and people with comorbidities (COPD, cardiology, nephrology). The most common causes of pneumonia are Streptoccocus pneumonia, Haemophilus influenzae, Moraxella catarrhalis and Mycoplasma pneumoniae. Based on the clinical picture, laboratory analyses, sputum analysis, scores (CURB65 and PSI), outpatient or hospital treatment is decided. Treatment is pharmacological and non-pharmacological. Medical treatment is combined antibiotic therapy according to the antibiogram, but empiric treatment is significantly more common. The importance of this topic is in the appropriate and adequate treatment of these patients, considering the still high mortality rate in the world of patients with pneumonia.